The Dead Sea Scrolls Today. Second edition. By James C. VanderKam - Brooke, George J. (The journal of theological studies, 2011)
The first edition (1994) of this trustworthy introduction to the Dead Sea Scrolls was translated into six languages and sold thousands of copies. The page layout is slightly different in this second edition, notably with pictures incorporated alongside the text as appropriate decoration throughout rather than printed as a separate collection of images, and overall 210 pages has become 260. The text has not simply been extended with a decade and a half of new information; rather, there are changes on almost every page, as the data are brought up to date and the tone adjusted.